Tinjauan Kelayakan Berbagai Teknik Penyediaan Air Dengan Kerangka Pemanfaatan Model Simulasi Penentuan Pola Tanam Pada Pertanian Lahan Kering - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Dry land in this study is defined as an unirrigated farmland, so that it gets the water only from rain or wells. It causes the harvest failures as the effect of limited water supply. To overcome this problem, it is necessary to find other alternatives for the water supply system that will be suitable for this land and meet the requirements of being effective and efficient. Under the condition, which are trickle irrigation and pouring system. These systems will irrigate the plants directly to the root zone, so the water will not be wasted and given only whenever it is needed. The feasibility of these techniques is determined from many aspects, those are: operation and maintenance, economic and social. Simulation of soil moisture balance with permanent wilting point as a constraint is used in this study to obtain the hydraulic dimension of these systems. This study used single cropping and intercropping pattern with four different kinds of upland crops. Data used for analysis comprise both primary and secondary data those are taken from Gunungkidul Regency. The simulation of soil moisture found out that the maximum deficit occurs at a combination of initial planting on July 20, 1997 and specific for peanut at single cropping pattern. The maximum was 38.75 mm equivalent for one meter soil depth. The result of feasibility analysis shows that there is significant difference for these two systems, so that they will have an equal performance to be considered. The value of IRR for trickle irrigation system is 24.45%, while for pouring system is 23.54%. On the other hand, there is inconcistency for benefit (B) and cost (C) parameters so that the value of (B - C) and B/C will not be appropriate to be taken as consideration in determining the better one. Based on IRR only, it can be concluded that the trickle irrigation system is more appropriate. Yet, the difference of IRR is very small, so that the operation and maintenance, and social aspect can also become important factors. For some alternatives with the same level of benefit, the choice by the user will really be the decisive factor.